The structure of the tetraploid sour cherry ‘Schattenmorelle’ (Prunus cerasus L.) genome reveals insights into its segmental allopolyploid nature - Wöhner, Thomas W.; Emeriewen, Ofere F.; Wittenberg, Alexander H. J.; Nijbroek, Koen; Wang, Rui Peng; Blom, Evert-Jan; Schneiders, Harrie; Keilwagen, Jens; Berner, Thomas; Hoff, Katharina J.; Gabriel, Lars; Thierfeldt, Hannah; et al. (Frontiers in Plant Science, 2023)
Sour cherry (Prunus cerasus L.) is an important allotetraploid cherry species that evolved in the Caspian Sea and Black Sea regions from a hybridization of the tetraploid ground cherry (Prunus fruticosa Pall.) and an unreduced pollen of the diploid sweet cherry (P. avium L.) ancestor. Details of when and where the evolution of this species occurred are unclear, as well as the effect of hybridization on the genome structure. To gain insight, the genome of the sour cherry cultivar ‘Schattenmorelle’ was sequenced using Illumina NovaSeqTM and Oxford Nanopore long-read technologies, resulting in a ~629-Mbp pseudomolecule reference genome. The genome could be separated into two subgenomes, with subgenome PceS_a originating from P. avium and subgenome PceS_f originating from P. fruticosa. The genome also showed size reduction compared to ancestral species and traces of homoeologous sequence exchanges throughout. Comparative analysis confirmed that the genome of sour cherry is segmental allotetraploid and evolved very recently in the past.